2019
DOI: 10.1038/s41598-019-56012-x
|View full text |Cite
|
Sign up to set email alerts
|

In search for the sources of plastic marine litter that contaminates the Easter Island Ecoregion

Abstract: Subtropical gyres are the oceanic regions where plastic litter accumulates over long timescales, exposing surrounding oceanic islands to plastic contamination, with potentially severe consequences on marine life. Islands’ exposure to such contaminants, littered over long distances in marine or terrestrial habitats, is due to the ocean currents that can transport plastic over long ranges. Here, this issue is addressed for the Easter Island ecoregion (EIE). High-resolution ocean circulation models are used with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 61 publications
0
19
0
1
Order By: Relevance
“…Many types of plastics are positively buoyant, and as passive particles they are transported by currents and concentrated in the large oceanic gyres (Maximenko et al, 2012;van Sebille et al, 2020). Dense accumulations of floating plastics, mainly from the mainland and industrial fisheries, are also found in the center of the South Pacific Subtropical Gyre (SPSG), which is close to Rapa Nui (Easter Island) (Eriksen et al, 2013(Eriksen et al, , 2018Miranda-Urbina et al, 2015;van Gennip et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many types of plastics are positively buoyant, and as passive particles they are transported by currents and concentrated in the large oceanic gyres (Maximenko et al, 2012;van Sebille et al, 2020). Dense accumulations of floating plastics, mainly from the mainland and industrial fisheries, are also found in the center of the South Pacific Subtropical Gyre (SPSG), which is close to Rapa Nui (Easter Island) (Eriksen et al, 2013(Eriksen et al, , 2018Miranda-Urbina et al, 2015;van Gennip et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In central and southern Chile, large amounts of plastics are also reaching the coastal waters through rivers(Rech et al, 2014;Rech et al, 2015). On oceanic islands and in oceanic waters, most recognizable marine litter items are plastics that come from the open ocean fisheries and the continental coast of South America(Kiessling et al, 2017;Luna-Jorquera et al, 2019;Miranda-Urbina, Thiel, & Luna-Jorquera, 2015), which is confirmed by a recent study using modelling techniques(van Gennip et al, 2019). The need for protecting oceanic islands through declaring them marine protected areas has been broadly accepted as a conservation tool for preserving the unique biodiversity they harbour.…”
mentioning
confidence: 79%
“…Petit, Campoy, Hevia, Gaymer, & Squeo, 2018). Plastic pollution, however, has reached the remote Chilean oceanic islands (Easter Island and Juan Fernandez), which receive huge volumes of marine litter coming from the continental coast of Chile and the industrial fishery (Luna-Jorquera et al, 2019;van Gennip et al, 2019). This opened a debate on whether these conservation instruments are sufficient to prevent plastics from entering protected areas (Barnes et al, 2018;Luna-Jorquera et al, 2019).…”
mentioning
confidence: 99%
“…Nevertheless, we lack information on how these materials spread, whether a gradient of contamination decreases away from terrestrial sources, or how, and for how long, they move into the deep sea. High resolution ocean circulation models (van Gennip et al, 2019), indicate a ∼2 year transit time of the litter produced in the western coast of South America, including debris produced by the industrial fishery operating in the high seas off Chile and Peru, to the center of the South Pacific Gyre. However, we lack any reliable estimate of the portion of this debris reaching the deep sea and the time it takes.…”
Section: Stratification By Anthropogenic Pressurementioning
confidence: 99%